Physiologic Midtreatment Tooth Movement as a Correction Strategy for Iatrogenic Root Exposure - Adith Venugopal; Paolo Manzano; M. Srirengalakshmi; Anand Marya; Nikhilesh R. Vaid; S. Jay Bowman (Case Reports in Dentistry)
In the case report showcased, we describe orthodontic treatment of a female patient with an excessive gingival display on smiling and severe dental crowding, with maxillary canines positioned excessively buccal (ectopic) to and in near transposition to the lateral incisors. The treatment involved extractions and initial use of unmitigated forces leading to excessive gingival thinning and buccal root positioning of the ectopic canines. Eventually, the root position was corrected and periodontal equilibrium was attained. On finishing the treatment, all objectives were achieved with a good esthetic outcome as well as excellent dental and occlusal relationships.